Physicochemical Decellularization of Bovine Pericardium: Effects on DNA Elimination, Extracellular Matrix Preservation, and Biocompatibility - Giorgi Filho, Rui C.; Martinez Junior, André Miguel [UNESP]; Calmon, Marilia F. [UNESP]; Tiera, Marcio José [UNESP]; Alvares, Dayane S.; Agreli, Guilherme; Nery, José G. [UNESP] (Springer Nature, 2024)
Bovine pericardium (BP) is an abundant waste biomass with applicability in tissue engineering, and decellularization is a requisite in enabling biocompatibility and suitability for medical applications. This study aimed to optimize bovine pericardium decellularization by integrating physical and chemical parameters while evaluating their effects on DNA elimination, extracellular matrix (ECM) preservation, and biocompatibility. Tissue-specific adaptations of known decellularization protocols were applied to enhance their efficacy and broaden their applicability in regenerative medicine and tissue engineering. The SD010 protocol, comprising freeze-thawing, agitation in a low-concentration (0.1% w/v) sodium deoxycholate (SD) solution, and thorough saline cleansing, emerged as a promising candidate for effective decellularization. Histological analysis revealed successful removal of cellular components, with SD010 exhibiting complete decellularization. DNA quantification indicated a significant reduction of DNA content in SD010-treated samples (85.7%). Scanning electron microscopy affirmed the preservation of ECM architecture posttreatment. Mechanical tests demonstrated minimal impact on the mechanical properties of treated tissues. The SD010 protocol’s potential for xenograft applications was supported by biocompatibility tests, as evidenced by increased cell proliferation in vitro. The results indicate a potentially efficient method for bovine pericardium decellularization, highlighting its utility for repurposing biomass waste materials produced by the food and health industry.Graphical Abstract